INTEGRATING CHARACTER EDUCATION AND LOCAL GENIUS THROUGH BALABOLKA IN TEACHING LISTENING - Herawati, Yayuk Widyastuti (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2016)
Nowadays, moral education is booming since there are many juvenile delinquencies in Indonesia. As the president began to worry and pointed us, as teachers, to hold the very crucial role in educating our students to prepare the future of Indonesia, we feel that some breakthrough on the media also should contain character education as well as local wisdom. This paper is aimed to give an alternative way in preparing media for teaching listening which can accommodate what we want. I propose balabolka software as the good choice for the needs of Indonesian students in general. Here, we can create our own media in the form of MP3 by inserting the important ingredients of character education, and local wisdom inside the content of our English teaching, especially teaching listening. By doing this, we expect that moral education and local wisdom which, obviously, can change our students behavior can be inserted in the English lesson, especially for listening skill.